Neuroprotective mechanisms of Ficus deltoidea in an Alzheimer’s disease-like rat model: targeting tau hyperphosphorylation through glycogen synthase kinase-3 beta and protein phosphatase 2a regulation - Manoharan, Sushmitaa Dhevii; Usman, Abdulhamid Sani; Abdul Hamid, Hafizah; Che Mohd Nassir, Che Mohd Nasril; Cheema, Manraj Singh; Che Ramli, Muhammad Danial; Mohd Moklas, Mohamad Aris; Mehat, Muhammad Zulfadli (Springer, 2026)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterised by memory loss, neurodegeneration, amyloid plaque accumulation and tau hyperphosphorylation. Dysregulation of glycogen synthase kinase-3β (GSK-3β) and protein phosphatase 2 A (PP2A) plays a pivotal role in tau pathology, contributing to synaptic dysfunction and memory impairment. Current AD medications offer limited palliative care, underscoring the need for multifaceted therapeutic strategies. Ficus deltoidea (FD), a medicinal plant renowned for its antioxidant and anti-inflammatory properties, has demonstrated neuroprotective effects, however, its specific role in modulating tau-associated proteins in AD remains underexplored. Thus, this study investigated the neuroprotective properties of FD on the spatial learning and memory, hippocampal histology and the levels of GSK-3β and PP2A in an AD-like rat model. Male rats were administered D-galactose (60 mg/kg) and aluminum chloride (200 mg/kg) for 11 weeks to induce AD-like characteristics. Rats were divided into six groups: control, AD model, donepezil-treated (1 mg/kg), and FD-treated groups receiving 50, 100 and 200 mg/kg of FD extract. Behavioural performances were assessed using the open field test (OFT) and modified elevated plus maze (mEPM). FD administration significantly improved spatial learning and memory in AD-like rats. Nissl staining revealed an increase in viable hippocampal granule neurons in FD-treated rats. Immunoblot analysis reported a reduction in GSK-3β and an increase in PP2A levels, suggesting reduced hippocampal tau phosphorylation. These findings indicate that FD confers neuroprotection by restoring the kinase-phosphatase balance, which in turn enhances hippocampal neuronal survival and memory, thereby supporting its potential as a phytotherapeutic agent for AD intervention.